The polis and the marvelous in the narrative of Herodotus - Azevedo, Flávia Lemos Mota de (Revista Archai, 2010)
The organization of the Herodotian narrative is based overall in the characterization of the despotism, however this can only mean something in Herodotus”Ÿ work if opposed to the Greek ways of political organization and mainly in relation to democracy. However, the fact that the barbarians”Ÿ despotism takes higher evidence in the work is enough to make the theme of tyranny dominate over the poliada organization? Could not we assume that the distinction of tyranny would not be only one way to show the Greeks their own particularity? In this case, the exotic one, marvelous and the admirable one would lie in the fact that the Greeks organized a completely singular way of political organization, stranger to all the other known peoples